2012
DOI: 10.1152/ajplung.00131.2011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the restricted α-subunit repertoire of airway smooth muscle GABAA receptors augments airway smooth muscle relaxation

Abstract: The prevalence of asthma has taken on pandemic proportions. Since this disease predisposes patients to severe acute airway constriction, novel mechanisms capable of promoting airway smooth muscle relaxation would be clinically valuable. We have recently demonstrated that activation of endogenous airway smooth muscle GABAA receptors potentiates ␤-adrenoceptor-mediated relaxation, and molecular analysis of airway smooth muscle reveals that the ␣-subunit component of these GABAA receptors is limited to the ␣4-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…Furthermore, the role of chloride regulation in ASM is not well understood and may be important in ASM contractility vs. relaxation (130). For example, a recent study showed that GABA, acting via the ionotropic GABA-A receptors can potentiate ␤ 2 ARmediated relaxation but in fact causes membrane depolarization involving chloride-mediated currents (78 ] i to, not only remain elevated, but also contribute to the remodeling process. Surprisingly, there are little to no data on the calmodulin-dependent plasma membrane Ca 2ϩ ATPase (PMCA; a major efflux mechanism in other cell types) beyond its localization to caveolae (52).…”
Section: L918mentioning
confidence: 99%
“…Furthermore, the role of chloride regulation in ASM is not well understood and may be important in ASM contractility vs. relaxation (130). For example, a recent study showed that GABA, acting via the ionotropic GABA-A receptors can potentiate ␤ 2 ARmediated relaxation but in fact causes membrane depolarization involving chloride-mediated currents (78 ] i to, not only remain elevated, but also contribute to the remodeling process. Surprisingly, there are little to no data on the calmodulin-dependent plasma membrane Ca 2ϩ ATPase (PMCA; a major efflux mechanism in other cell types) beyond its localization to caveolae (52).…”
Section: L918mentioning
confidence: 99%
“…Immortalized and primary human ASM cell lines were prepared as described previously (23,24) and grown in phenol red-free Dulbecco's modified Eagle's medium/F12 media (GIBCO, Grand Island, NY) with 10% fetal bovine serum and antibiotics. , solid squares), 6-gingerol (100 mM, solid triangles), 8-gingerol (100 mM, open circles), or 6-shogaol (100 mM, open triangles) was added concurrently with the 300 pM concentration of isoproterenol.…”
Section: Cell Culturementioning
confidence: 99%
“…Immortalized and primary human ASM cell lines were prepared as described previously (17,18) and grown in phenol red-free Dulbecco's Modified Eagle's Medium/F12 media (GIBCO, Grand Island, NY), with 10% FBS and antibiotics.…”
Section: Cultured Human Airway Smooth Muscle Cellsmentioning
confidence: 99%